Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kualitas Pelanggan (Study Kasus PT Mirakuru Abadi Sejahtera Jakarta Utara) - Sari, Hernanda; Heriyanto, Yayak (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This One of the most crucial elements within an organization is its service excellence in an organization or company is key to its success inconfronting the challenges and threats that may impede its future growth. PT. Mirakuru Abadi Sejahtera markets its mocha ice cream products through an electronic or online network. Miwaku Mochi Ice Cream Indonesia ensures product quality by using high-quality ingredients and employing modern technology to craft mocha ice cream with a smooth texture and delightful flavor. This research aims to analyze the influence of product quality and service quality on customer satisfaction at PT.Mirakuru Abadi Sejahtera in North Jakarta. The research employs a quantitative descriptive approach, and primary data is collected through questionnaire distribution to customers. Primary data analysis utilizes statistical analysis with SPSS version 25. The research findings demonstrate that Product Quality significantly affects Customer Satisfaction by 67.8%, whereas Service Quality significantly influences Customer Satisfaction by 77.8%. Simultaneously, both Product Quality and Service Quality significantly impact Customer Satisfaction at 79.7%, with the remaining 20.3% influenced by other unaccounted factors.